Confessions of an Iyeska - Burnette, Viola, 1939- (Book collections on Project MUSE., 2018)
"The memoirs of a Lakota woman who rose from humble beginnings, overcoming hardship to attain a prominent position as a judge, legal activist, and spokesperson for her people"--Provided by publisher.